ADAT NATIONAL PARK AS LEGAL POLITICS OF LIVING SPACE OF ANAK DALAM TRIBE - Erwin, Muhamad; Yusriyadi, Yusriyadi (Fakultas Hukum, Universitas Diponegoro, 2024)
The Anak Dalam Tribe in Bukit Dua Belas National Park faces significant challenges due to conflicting paradigms between state control over national parks and customary land rights which sacrifice the interest of Anak Dalam Tribe. This study underscores the urgent need for a shift in the conservation legal paradigm to safeguard the tribe's living space. Employing a non-doctrinal research method, it examines law as a social reality within the tribe's habitat. The findings advocate for a new conservation model termed